Tapping into the endocannabinoid system to ameliorate acute inflammatory flares and associated pain in mouse knee joints - Krustev, Eugene (BioMed Central, 2014)
INTRODUCTION: During the progression of rheumatoid arthritis (RA), there are frequent but intermittent flares in which the joint becomes acutely inflamed and painful. Although a number of drug therapies are currently used to treat RA, their effectiveness is variable and side effects are common. Endocannabinoids have the potential to ameliorate joint pain and inflammation, but these beneficial effects are limited by their rapid degradation. One enzyme responsible for endocannabinoid breakdown is fatty acid amide hydrolase (FAAH). The present study examined whether URB597, a potent and selective FAAH inhibitor, could alter inflammation and pain in a mouse model of acute synovitis. METHODS: Acute joint inflammation was induced in male C57BL/6 mice by intra-articular injection of 2% kaolin/2% carrageenan. After 24 hr, articular leukocyte kinetics and blood flow were used as measures of inflammation, while hindlimb weight bearing and von Frey hair algesiometry were used as measures of joint pain. The effects of local URB597 administration were then determined in the presence or absence of either the cannabinoid (CB)1 receptor antagonist AM251, or the CB2 receptor antagonist AM630. RESULTS: URB597 decreased leukocyte rolling and adhesion, as well as inflammation-induced hyperaemia. However, these effects were only apparent at low doses and the effects of URB597 were absent at higher doses. In addition to the anti-inflammatory effects of URB597, fatty acid amide hydrolase (FAAH) inhibition improved both hindlimb weight bearing and von Frey hair withdrawal thresholds. The anti-inflammatory effects of URB597 on leukocyte rolling and vascular perfusion were blocked by both CB1 and CB2 antagonism, while the effect on leukocyte adherence was independent of cannabinoid receptor activation. The analgesic effects of URB597 were CB1 mediated. CONCLUSIONS: These results suggest that the endocannabinoid system of the joint can be harnessed to decrease acute inflammatory reactions and the concomitant pain associated with these episodes.